Innovative Attitudes and Size of Companies - Dimitrova, Yanica (Research Papers, 2020)
The focus of the article is to uncover the link between the size of firms and their attitudes to innovation that contribute to enhancing competitiveness. Methodology: Analysis of related research-related literature; analysis of results from a representative survey conducted under the project "National Business Survey - July-August, 2015", based on a sample of 1000 companies. Results: Among the Bulgarian business, the tendency to innovate, regardless of the size of the company, still lacks broad support. The focus is on acquiring tangible assets. Conclusions: Attitude towards innovation are more decisive than companies’ size. Originality: By our knowledge, no such research has been carried out in Bulgaria.